In-hospital mortality and major complications related to radiofrequency catheter ablations of over 10 000 supraventricular arrhythmias from 2005 to 2020: individualized case analysis of multicentric administrative data. Issue 1 (25th August 2022) - Doldi, Florian; Geßler, Nele; Anwar, Omar; Kahle, Ann-Kathrin; Scherschel, Katharina; Rath, Benjamin; Köbe, Julia; Lange, Philipp Sebastian; Frommeyer, Gerrit; Metzner, Andreas; Meyer, Christian; Willems, Stephan; et al.
Abstract: Aims: The incidence of in-hospital post-interventional complications and mortality after ablation of supraventricular tachycardia (SVT) vary among the type of procedure and most likely the experience of the centre. As ablation therapy of SVT is progressively being established as first-line therapy, further assessment of post-procedural complication rates is crucial for health care quality. Methods and results: We aimed at determining the incidence of in-hospital mortality and bleeding complications from SVT ablations in German high-volume electrophysiological centres between 2005 and 2020. All cases were registered by the German Diagnosis Related Groups—and the German Operation and Procedure Classification (OPS) system. A uniform search for SVT ablations from 2005 to 2020 with the same OPS codes defining the type of ablation/arrhythmia as well as the presence of a vascular complication, cardiac tamponade, and/or in-hospital death was performed. An overall of 47 610 ablations with 10 037 SVT ablations were registered from 2005 to 2020 among three high-volume centres. An overall complication rate of 0.5% ( n = 38) was found [median age, 64; ±15 years; female n = 26 (68%)]. All-cause mortality was 0.02% ( n = 2) and both patients had major prior co-morbidities precipitating a lethal outcome irrespective of the ablation procedure. Vascular complications occurred in 10 patients (0.1%), and cardiac tamponade was detected in 26 cases (0.3%). Conclusion: The present case-based analysis shows an overall low incidence of in-hospital complications after SVT ablation highlighting the overall very good safety profile of SVT ablations in high-volume centres. Further prospective analysis is still warranted to guarantee continuous quality control and optimal patient care.